Autophagy and Inflammation Regulation in Acute Kidney Injury - Gong, Li; Pan, Qingjun; Yang, Nianlan (Frontiers in Physiology, 2020)
Autophagy at an appropriate juncture in the cell cycle exerts protective effects in acute kidney injury (AKI), whereas abnormal autophagy may lead to cell death. Inflammatory response plays a pivotal role in the pathophysiological process of kidney injury and repair during AKI. Several studies have reported an interaction between autophagy and inflammation in the pathogenesis of AKI. This review outlines recent advances in the investigation of the role of autophagy in inflammatory response regulation based on the following aspects. (1) Autophagy inhibits inflammatory responses induced in AKI through the regulation of mTOR and AMPK pathways and the inhibition of inflammasomes activation. (2) Autophagy can also help in the regulation of inflammatory responses through the nuclear factor kappa B pathway, which is beneficial to the recovery of kidney tissues. These studies reviewed here provide better insight into the mechanisms underlying the protective effects of the autophagy-inflammatory pathway. Through this review, we suggest that the autophagy-inflammatory pathway may serve as an alternative target for the treatment of AKI.